Suppression mechanism of weld appearance defects in tandem TIG welding by numerical modeling - Guoliang Qin; Chao Feng; Hong Ma (Journal of Materials Research and Technology, 2021)
In high-speed tungsten inert gas (TIG) welding, the premature solidification of liquid metal in low-temperature zone of molten pool results in the formation of weld appearance defects (WADs) such as undercut and humping weld. Tandem TIG welding was developed to prevent the formation of the WADs and realize high-speed welding. A three-dimensional model of arc and molten pool was developed to investigate the heat and mass transfer behavior in molten pool of tandem TIG welding process. The results indicate that, because of the thermo-mechanical control effect on the molten pool by the assistant TIG arc, a stable swelling zone forms between the two arcs and the formation of trail accumulation was prevented. The maximum backward velocity driven by the main TIG arc is decreased significantly, which suppresses the backward flow and premature solidification of liquid metal. The existence time of liquid metal is evidently longer by 70% than that of single TIG welding, which leads to the liquid flow at the tail of weld pool sufficiently moving forward to suppress the instability of depression zone. The heat and mass transfer in molten pool indicates that during tandem TIG welding process, the thermo-mechanical effect of assistant TIG arc prolongs the existence time of liquid metal and improves its flowing back, so the WADs were efficiently suppressed.